Legal Certainity of The Probationary Period Regulation For Employees of Regional Water Company - ratnawati; Abdul Rachmad Budiono; Hamidi Masykur (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The legal conflict regarding the probationary period between the Employment Law and the Ministry of Home Affairs Regulation concerns the regulation of the probationary period, where the Employment Law stipulates that the probationary period should not exceed 3 (three) months. However, the Ministry of Home Affairs Regulation states a minimum of 3 months and a maximum of 6 months for the probationary period. Based on this, the research question of this paper is formulated as follows: What are the provisions of the Probationary Period in Article 33 Paragraph (2) of the Minister of Home Affairs Regulation on the Organization and Personnel of Regional Drinking Water Companies in terms of the Principle of Legal Certainty? The writing of this paper uses a normative juridical method with the Statue Approach and Analytical Approach. In analysing this research, several theories are employed, including the theory of legal certainty, the theory of norm hierarchy, and the theory of norm conflict. The researcher obtains answers to the existing problems by analysing the legal certainty of the probationary period regulation. In terms of the theory of legal certainty by Jan Michiel Otto, it aligns with Lord Lyod's opinion on the meaning of legal certainty, which is consistent, stable, and clear. The regulation in Article 33 Paragraph (2) of the Ministry of Home Affairs Regulation does not meet the principle of legal certainty. While the regulation in the Ministry of Home Affairs Regulation in Article 33 Paragraph (2) is consistent and clear, it lacks consistency. This is because the regulation should comply with labour laws where the maximum probationary period is 3 months, while in the Ministry of Home Affairs Regulation, the probationary period is a minimum of 3 months and a maximum of 6 months.